Environmental Justice at the Environmental Regulation in Indonesia and Uzbekistan - Hudali Mukti; Bobur Baxtishodovich Sobirov (Lembaga Contrarius Indonesia, 2023)
Justice theory, which emphasizes the fair and equitable allocation of risks and benefits, has significantly influenced the idea of environmental justice. Indonesia and Uzbekistan have made it mandatory for laws and regulations to implement the concept of environmental justice. Still, in practice, the rules created give birth to social-environmental conflict dimensions that are increasingly prevalent and far removed from environmental justice. This research aims to understand and analyze environmental justice regulation in Indonesia and Uzbekistan. This research uses a normative juridical approach with a literature review involving primary and secondary legal sources. The results show that the provisions of the Job Creation Bill in the forestry and environmental sectors negate access to justice via litigation at the State Administrative Court (PTUN) so that there is no public space to continue an AMDAL decision or environmental approval as part of an environmental licensing instrument in the realm of administrative law. Regulatory problems that co-occur and are followed by implementation problems at a later date relating to the legitimacy and protection of people's constitutional rights will harm the community's sense of justice. At the same time, the issue of environmental injustice in Uzbekistan arises from the ecological crisis beginning with green space, waste management, and the water crisis that has afflicted the nation, as indicated by the preceding explanation. The government must establish national policies, institutional instruments, and central and regional environmental management authorities to facilitate development with an eye toward environmental justice.